In Vitro Biotransformation of Total Glycosides in Qiwei Baizhu Powder by the Gut Microbiota of Normal and Diarrheal Mice: Novel Insight Into the Biotransformation of Multi-Glycosides by the Gut Microbiota - Xie, Guozhen; Zhou, Rongrong; Huang, Lili; Zhang, Shuihan; Tan, Zhoujin (Frontiers in Chemistry, 2022)
The gut microbiota (GM) is involved in the metabolism of glycosides and is beneficial for enhancing their bioactivity. However, the metabolism of multi-glycosides by the GM under normal and pathological conditions is unclear. In this study, the total glycosides (TG) of the traditional Chinese medicine (TCM) formula Qiwei Baizhu Powder (QWBZP) were extracted to represent a multi-glycoside system. Ultra-high-performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UHPLC-Q-TOF-MS/MS) was used to rapidly identify the components and in vitro metabolites of QWBZP-TG. The metabolic profiles of QWBZP-TG in the GM of normal and diarrheal mice were also compared. A total of 68 compounds and seven metabolites were identified in the QWBZP-TG and metabolic samples, respectively. Deglycosylation was the main metabolic pathway of in vitro multi-glycoside metabolism. Liquiritin apioside, isoliquiritin apioside, liquiritin, protopanaxadiol (PPD)-type, and oleanane (OLE)-type ginsenosides were relatively easy to metabolize by the GM. At first, the deglycosylation capability of the GM of normal mice was superior to that of diarrheal mice, but the deglycosylation capability of diarrheal mice gradually recovered and produced abundant deglycosylation metabolites. In conclusion, deglycosylation metabolites may be the bioactive components of QWBZP. Glycoside-bacteria interaction may be a key mechanism for QWBZP to therapy diarrhea.